Pro-tourism and anti-tourism community groups at a world heritage site in Turkey - Olya, Hossein G. T.; Shahmirzdi, Esmaeil Khaksar; Alipour, Habib (Routledge Journals, Taylor & Francis Ltd, 2019)
This empirical study deepens our understating of support for sustainable tourism development (SSTD) from the perspectives of various community groups in Pamukkale, a world natural and cultural heritage inscribed on the UNESCO list. A quota sampling technique was used to survey the views of three communities: business, farmers, and the government. Occurrences of contrarian cases were checking using cross-tabulation analyses. Complexity theory and fuzzy-set qualitative comparative analysis (fsQCA), as an innovative approach, were applied to develop and test a configurational model for predicting both high and low SSTD scores for three community groups. The fsQCA results revealed that causal recipes for achieving pro-tourism behaviour are not simply mirror opposites of the conditions leading to anti-tourism behaviour. The complex configurational models indicating high/low SSTD were unique to each community group, indicating that a specified strategy must be developed for community-based tourism management. The evidence-of-fit validity of the measurement model and the predictive validity of the configurational model were provided. Support for the fsQCA results in the key tenets of complexity theory confirms that this theory explained the heterogeneity and complex interactions of SSTD antecedents well. The study outcomes provide a guideline for managing conditions to both increase SSTD and hinder SSTD negation for various community groups. The limitations and implications for further research are discussed.
Keywords: community; tourism support; complexity theory; configuration; predictive validity; Pamukkale